2021
DOI: 10.1093/noajnl/vdab103
|View full text |Cite
|
Sign up to set email alerts
|

Generation, characterization, and drug sensitivities of 12 patient-derived IDH1-mutant glioma cell cultures

Abstract: Background Mutations of the isocitrate dehydrogenase (IDH) gene occur in over 80% of low-grade gliomas and secondary glioblastomas. Despite considerable efforts, endogenous in vitro IDH-mutated glioma models remain scarce. Availability of these models is key for the development of new therapeutic interventions. Methods Cell cultures were established from fresh tumor material and expanded in serum-free culture media. D-2-Hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…During characterization of the glioma cultures, a similar observation was made at the RNA level. 14 In this characterization study, RNAseq results showed minimal changes between IDH1 wt and IDH1 mut cultures for the genes related to the proteins in our metabolic proteomics panel. In addition, a correlation between the RNAseq and proteomics data was observed.…”
Section: ■ Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…During characterization of the glioma cultures, a similar observation was made at the RNA level. 14 In this characterization study, RNAseq results showed minimal changes between IDH1 wt and IDH1 mut cultures for the genes related to the proteins in our metabolic proteomics panel. In addition, a correlation between the RNAseq and proteomics data was observed.…”
Section: ■ Discussionmentioning
confidence: 59%
“…This shows that even though limited significant changes were observed in the metabolic panel, the proteome as a whole is quite different between the two sample groups. A further description of the differences between the IDH1 wt and IDH1 mut primary cell cultures is published by Verheul et al 14 To confirm the IDH1 mutation in the samples, a PRM analysis was performed using several peptides from IDH1, including peptides with and without the mutation. The IDH1 mutation changes the arginine (R) on the wild-type "PIIIGR" peptide of which the equivalent in the IDH1 R132H mutated form is peptide "PIIIGHHAYGDQYR" (Figure 4).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 101 , 102 , 106 , 177 , 178 , 179 These cell lines provide relatively stable models to study the effects of the presence of the mutIDH1/2 enzymes, but it is possible that the process of producing the model itself may have unknown metabolic consequences and that these models do not account for some genetic and, subsequently, metabolic differences between WT IDH and mutIDH1/2 gliomas. 180 , 181 , 182 A limited number of glioma cell lines that endogenously express mutIDH have been successfully cultured from grade II astrocytomas, 183 grade III gliomas, and what were formerly known as secondary GBMs. 174 , 183 , 184 , 185 , 186 PDX mouse models bearing cells with IDH1/2 mutations derived from affected individuals are potentially more physiologically relevant than cell culture using immortalized cell lines.…”
Section: Idh Mutant and Wt Cancer Modelsmentioning
confidence: 99%
“… 180 , 181 , 182 A limited number of glioma cell lines that endogenously express mutIDH have been successfully cultured from grade II astrocytomas, 183 grade III gliomas, and what were formerly known as secondary GBMs. 174 , 183 , 184 , 185 , 186 PDX mouse models bearing cells with IDH1/2 mutations derived from affected individuals are potentially more physiologically relevant than cell culture using immortalized cell lines. 181 , 187 , 188 Several PDX-specific mutIDH1 glioma cell lines have been established, 99 , 188 , 189 but in comparison with cultured cells, these can be less practical and straightforward to work with.…”
Section: Idh Mutant and Wt Cancer Modelsmentioning
confidence: 99%